Genetic findings of children with congenital heart diseases using chromosomal microarray and trio-based whole exome sequencing - Guo, Rui; Duan, Chunhong; Zarrei, Mehdi; Reuter, Miriam S.; Dong, Rui; Zhang, Guangye; Yang, Xiaomeng; Zhang, Haiyang; Wang, Ying; Scherer, Stephen W.; Liu, Yi; Gai, Zhongtao (Scientific reports, 2025)
Congenital heart disease (CHD) is the most common type of birth defects in humans. Genetic factors have been identified as an important contributor to the etiology of CHD. However, the underlying genetic causes in most individuals remain unclear. Here, 101 individuals with CHD and their unaffected parents were included in this study. Chromosomal microarray analysis (CMA) as a first-tier clinical diagnostic tool was applied for all affected individuals, followed by trio-based whole exome sequencing (WES) of 76 probands and proband-only WES of 3 probands. We detected aneuploidies in 2 individuals (trisomy 21 and monosomy X), 21 pathogenic and likely pathogenic copy number variants (CNVs) in 19 individuals, and pathogenic and likely pathogenic SNVs/InDels in 8 individuals. The combined genetic diagnostic yield was 28.7%, including 20.8% with chromosomal abnormalities and 7.9% with sequence-level variants. Eighteen CNVs in 17 individuals were associated with 13 recurrent chromosomal microdeletion/microduplication syndromes, the most common being 22q11.2 deletion syndrome. Pathogenic/likely pathogenic sequence-level variants were identified in 8 genes, including GATA6 , FLNA , KANSL1 , TRAF7, KAT6A , PKD1L1 , RIT1 , and SMAD6 . Trio sequencing facilitated the identification of pathogenic variation (55.6% were de novo missense variants). In individuals with extracardiac features, the overall detection rate was significantly higher (61.5%) than in individuals with isolated CHD (17.3%) ( P = 4.6 × 10 − 3 ). Our study further emphasized the importance of combining CMA and trio-WES for clinical genetic testing of individuals with CHD. Trio-based WES should be part of the diagnostic algorithm.